PENGARUH PENGGUNAAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DAN MOTIVASI TERHADAP HASIL BELAJAR EKONOMI SISWA KELAS XI IIS MAN 1 LOMBOK BARAT - Agus Setiyono (VALUTA, 2022)
This research is motivated by the low learning outcomes of students in several subjects. One of them is economics. One of the efforts that can be done to overcome these problems is the use of Problem Based Learning learning strategies in learning. The purpose of this research is to reveal the effect of problem based learning learning model and motivation on students' economic learning outcomes. The type of research used is Quasi Experiment using a 2x2 factorial design. The population in this study were students of class XI IIS-1 MAN 1 West Lombok, NTB for the 2021/2022 school year. The sample of this study was selected by simple random sampling technique with the results of students in class XI IIS-1 MAN 1 West Lombok as samples. The research data were obtained from the results of the economics study test and a learning motivation questionnaire. Data analysis was performed using the t-test and Two-Way ANOVA. The results showed that the economic learning outcomes of students who were taught using the problem based learning model were better than those of students who were taught using conventional learning. This also applies to students who have high and low motivation. Economic Learning Outcomes (cognitive, affective, and psychomotor) students who have high motivation who are taught by PBL learning model are better than students who have high motivation who are taught by conventional learning. The same thing is also shown in students who have low motivation and are taught with the PBL learning model looks better than students with low motivation who are taught by conventional learning.